Indonesian Throughflow drove Australian climate from humid Pliocene to arid Pleistocene. Issue 13 (7th July 2017) - Christensen, Beth A.; Renema, Willem; Henderiks, Jorijntje; De Vleeschouwer, David; Groeneveld, Jeroen; Castañeda, Isla S.; Reuning, Lars; Bogus, Kara; Auer, Gerald; Ishiwa, Takeshige; McHugh, Cecilia M.; Gallagher, Stephen J.; et al.
Abstract: Late Miocene to mid‐Pleistocene sedimentary proxy records reveal that northwest Australia underwent an abrupt transition from dry to humid climate conditions at 5.5 million years (Ma), likely receiving year‐round rainfall, but after ~3.3 Ma, climate shifted toward an increasingly seasonal precipitation regime. The progressive constriction of the Indonesian Throughflow likely decreased continental humidity and transferred control of northwest Australian climate from the Pacific to the Indian Ocean, leading to drier conditions punctuated by monsoonal precipitation. The northwest dust pathway and fully established seasonal and orbitally controlled precipitation were in place by ~2.4 Ma, well after the intensification of Northern Hemisphere glaciation. The transition from humid to arid conditions was driven by changes in Pacific and Indian Ocean circulation and regional atmospheric moisture transport, influenced by the emerging Maritime Continent. We conclude that the Maritime Continent is the switchboard modulating teleconnections between tropical and high‐latitude climate systems. Key Points: Northwestern shelf sediments record major shifts in Australian climate at 5.5, 3.3, and 2.4 Ma We interpret NGR‐derived proxies as changes in terrestrial climate from annually to seasonally wet Neogene Australian climate is defined by the progressive restriction of ITF by the Maritime Continent Plain Language Summary: Australia is the most arid habitable continent on earth, however its climate is capable of dramatic change with seasonal monsoon rains in the otherwise arid northwest. We analyzed natural gamma radiation in a recently drilled borehole (IODP Expedition 356 Site U1463) off NW Australia to examine long‐term climate changes over the last 6 million years. Based on variations in potassium, thorium and uranium, as well as common clay minerals, we show that the NW continent was more humid during the Pliocene period, between ~5.5 and 3.3 million years ago (Humid Interval), and became arid by the early Pleistocene, ~2.4 million years ago (Arid Interval). We attribute the Humid Interval to an expansion of warm surface waters in the western Pacific, supplying warm and moist air to the continent. As Australia moved north, the Maritime Continent (islands to the north) emerged, restricting the flow of warm surface currents from the Pacific (Indonesian Throughflow), resulting in drier conditions on land. The Arid Interval ushered in a modern‐like Australian climate, with seasonal rainfall and dust storms, and a more modern Indian Ocean circulation. Our results show that the Maritime Continent is an important control on both Australian climate and Indian Ocean circulation.